Wines of Baja Mexico: A qualitative study examining viticulture, enology, and marketing practices - Jorge Covarrubias; Liz Thach (Wine Economics and Policy, 2015)
Mexico has been producing wine since the 1500, yet very little is known about their viticulture, enology, and marketing practices. This qualitative research study was designed to shed more light on these issues. Based on 10 in-depth interviews with winery owners and winemakers in the Valle de Guadualupe of the Baja Peninsula, where the majority of Mexican wineries are located, this study describes viticulture, enology, and marketing practices for Baja wines. It concludes with a discussion on the future of Mexican wines.
Keywords: 330; Economics; Marketing; Mexico; Viticulture; Wine